The Role of Parents in Strengthening the Character of Honesty When Learning at Home during the Covid-19 Pandemic - Pratiwi, Putri Hardina; Murdiono, Mukhamad (Universitas Serambi Mekkah, 2020)
This study aims to describe how the role of parents in strengthening the character of honesty when learning at home during the Covid-19 pandemic. To achieve this goal, a qualitative research approach was used with a case study research design. The research subjects are 3 parents lived in Gedang Kulut Village, Cerme District, Gresik Regency. The instruments used to collect data in this study were observation and in-depth interviews. The data were analyzed using an interactive analysis model proposed by Miles and Huberman. The results of the data analysis show that the strengthening of the character of honesty when learning at home is still weak. This can be seen from the behavior of children who are still not honest to their teachers when working on assignments, midterm tests and final exams. The low character of honesty possessed by children is caused by a lack of independent character and still relying on their parents to do the schoolwork. Character strengthening was carried out by parents to their children by providing exemplary, motivation and punishment. Exemplary is given to children by providing examples of good character, motivation is carried out by providing examples of positive behavior when the child does not have an enthusiasm for learning and wants to do a dishonest behavior. Lastly, the punishment is given when the child cannot behave honestly to their parents, teachers, and themselves. Indirectly, the three strategies of honesty character strengthening certainly have a profound impact on the child's growth process while learning at home in the Covid-19 pandemic.Â Keywords: Role of Parents, Honesty, Covid-19.